Q: Factor the trinomial x2 plus 9x plus 14?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

(x - 6)(x - 3)

9x+3

If you mean: 2x^2 +9x +7 then it is (2x+7)(x+1) when factored

2x2+9x+9 = (2x+3)(x+3) when factored

(x^2 + 9x +14) / (x+5) Factor (x^2 + 9x +14) [(x+7)(x+2)]/[(x+5)], x cannot equal -5

Related questions

10 + 9x

(x - 6)(x - 3)

No. It is 9x, which is a monomial.

9x+3

If you mean: 2x^2 +9x +7 then it is (2x+7)(x+1) when factored

2x2+9x+9 = (2x+3)(x+3) when factored

(x^2 + 9x +14) / (x+5) Factor (x^2 + 9x +14) [(x+7)(x+2)]/[(x+5)], x cannot equal -5

102 +9x +4 = 9x + 106, which is in its simplest form.

If a trinomial is a perfect square, then the discriminant will equal 0. The discriminant is equal to B^2-4AC. The variables come from the standard form of a quadratic which is Ax^2+Bx+C In this problem, A=81, B=-72, and C=16 so the discriminant is: (-72)^2-4(81)(16)=5,184-5,184=0 so this is a perfect square trinomial. To factor, notice that 81=9^2 and 16=4^2, so 81x^2=(9x)^2. We can then factor the trinomial into (9x+4)(9x-4)

9x + 2 = 12x + 14 -3x = 12 x = -4

You don't need to factor that; you can add them together, since they have the same variable.However, assuming you might mean 81x squared + 9x, you can take out the common factor, which is 9x.

9x2+11x-14 = (9x-7)(x+2) when factored with the help of the quadratic equation formula.